ANALYSIS OF THE INFLUENCE OF SOME TECHNOLOGICAL FACTORS AND COMPARATIVE EFFICIENCY OF THEIR APPLICATION ON YIELD POTENTIAL OF TWO ISOGENIC WHEAT LINES UNDER THE CONDITIONS OF SOUTHERN ROMANIA - Ovidiu PĂNIȚĂ; Paula IANCU; Marin SOARE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the conditions of southern Romania, on a chernozem type soil, without irrigation, for 3 years, 2 isogenic lines of wheat, M1 and M2, with different biological yield potential were analyzed. The analyzed factors were: Nitrogen fertilization doses, Phosphorus fertilization doses and sowing density. Concerning the influence of nitrogen on yield, all calculated average values differ significantly from each other, both for M1 and for M2, the highest average values being recorded at a dose of N150 kg a.s./ha. Regarding the influence of phosphorus on seed yield, both for M1 and M2, no significant differences are recorded between the two averages values calculated for the analyzed graduations. Related to the influence of density on seed yield, the average value recorded at 700 g.s./m2, records significant differences compared to the value averages recorded at the density of 500 g.s./m2, between the value averages recorded on 600 g.s./m2 and the other value averages, no statistically differences being recorded. Concerning the trend models between Nitrogen doses and wheat yield, all the models are mathematically correct, what differs is the regression coefficient. The regression coefficient is higher under phosphorus fertilization and on high sowing density.